PENDAMPINGAN MANAJEMEN SISTEM PEMASARAN UNTUK MENINGKATKAN KUALITAS BERSAING USAHA CHICK’N CRUNCH STICK - Retno Muslinawati; Sutrisno; Samsul Arif; Vico Satria Rizky (Universitas Kadiri, 2026)
Small and medium enterprises (SMEs) play a vital role in local economic growth in Bojonegoro Regency, but many still face challenges in marketing, financial management, and branding. Chick'n Crunch Stick, an SME with culinary potential, faces similar challenges in expanding its market, managing financial records, and building a professional business image. This mentoring program aimed to enhance the partner's capacity by strengthening digital marketing, improving financial management, and developing a more consistent brand identity. The program adopted a participatory approach through observation, needs analysis, training, mentoring, and evaluation. The mentoring results showed that the partner successfully implemented digital marketing through the TikTok platform, adopted digital financial recording using the Kasir Pintar application, and improved marketing management and financial administration. These interventions enhanced the partner’s managerial capacity, strengthened promotional activities, and improved business competitiveness in the local market. The findings indicate that participatory mentoring can improve the managerial capacity and competitiveness of SMEs through the integration of digital marketing and digital financial management.